'Employ Your Mind': a pilot evaluation of a programme to help people with serious mental illness obtain and retain employment. (February 2021) - Miles, Anne; Crosse, Caroline; Jenkins, Zoe; Moore, Gaye; Fossey, Ellie; Harvey, Carol; Castle, David
Objective: Cognitive impairments contribute to difficulty in obtaining employment for people with severe mental illnesses (SMIs). We describe a pilot evaluation of a programme, Employ Your Mind (EYM), which integrates cognitive remediation therapy (CRT) with vocational rehabilitation. Method: Sixty participants with SMIs enrolled in EYM, a 6-month programme that combines CRT exercises, individual project work and group reflection sessions about social interaction and cognitive functioning. Participants completed assessments of cognitive function (Audio Recorded Cognitive Screen, Wechsler Digit Span Task), psychosocial function (Work and Social Adjustment Scale, General Self-Efficacy Scale) and abilities related to work (Dialogue about Working Ability, Self-Assessment of Thinking Skills) at baseline and postprogramme. Paired t- tests were used to compare assessments of participants who completed the programme between the two time points. Results: The programme was completed by 22 individuals. These individuals demonstrated significant improvement in cognitive function, social and work-related function, and subjective thinking ability after completing the EYM programme. Conclusion: The EYM programme is effective in improving cognition, impairments related to work and social function, and subjective thinking skills for some individuals with SMIs. Future evaluation of the programme should focus on enhanced retention and assessment of employment outcomes.